PENGARUH DEVIDEND PER SHARE, RETURN ON EQUITY, DAN PRICE TO BOOK VALUE PADA RETURN SAHAM - Karlina, Ni Wayan Sri; Widanaputra, AAGP (E-Jurnal Akuntansi, 2016)
The purpose of this study was to examine the effect on a fundamental analysis of stock returns mananufaktur company listed on the Indonesia Stock Exchange 2011-2014 period. Independent variables tested are dividend per share (DPS), return on equity (ROE), and price to book value (PBV), while the dependent variable in this study is the stock return. These samples included 156 companies with purposive sampling method. Data was collected by using non-participant observation. Data were analyzed using multiple linear regression analysis technique. The test results showed that the dividend per share (DPS), return on equity (ROE), and price to book value (PBV) positive effect on stock returns.
Keywords: devidend per share (DPS), return on equity (ROE), price to book value (PBV), dan return saham